2020
DOI: 10.1002/joec.12149
|View full text |Cite
|
Sign up to set email alerts
|

Resiliency, Self‐Regulation, and Reemployment After Job Loss

Abstract: This study investigated self-regulation and resiliency in one's search for reemployment. Although trait-based approaches are central to many resiliency conceptualizations, recent research has found that self-regulation (affective, behavioral, and cognitive) contributes to predicting resiliency-related outcomes. We hypothesized that selfregulation would incrementally predict reemployment process outcomes, specifically the job search outcomes of psychological well-being, job search self-efficacy, and job search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Participants in our study demonstrated personal lifestyle adjustments to persevere through challenging circumstances via internal coping mechanisms. Existing literature has shown that self‐regulation processes are a part of resilience, and both serve as protective factors while individuals are recovering from adversities such as job loss (McLarnon et al, 2020 ; Prescod & Zeligman, 2018 ). In addition, participants adjusted their internal coping strategies because of the new financial constraints, personal and familial needs, and quarantine mandates relating to COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study demonstrated personal lifestyle adjustments to persevere through challenging circumstances via internal coping mechanisms. Existing literature has shown that self‐regulation processes are a part of resilience, and both serve as protective factors while individuals are recovering from adversities such as job loss (McLarnon et al, 2020 ; Prescod & Zeligman, 2018 ). In addition, participants adjusted their internal coping strategies because of the new financial constraints, personal and familial needs, and quarantine mandates relating to COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Complementarily, self-regulation has shown a significant, negative association with poor sleep quality in an average university population, as well as negative predictive value of smartphone addiction [ 11 ]. Levels of self-regulation have also been found to correlate positively with degree of well-being [ 12 ]. Recent studies have proposed self-regulation as an explanatory cross-diagnostic variable, where different diagnostic categories converge [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Referred to as adapting to the new normal during the COVID-19 pandemic, the ability to cope and manage permanent and temporary change is a behavioral task that must be mastered. Similar attention is also required to help unemployed individuals avoid experiencing societal stigmas associated with their job loss and subsequent psychosocial state (Amundson & Borgen, 1987;Guindon & Smith, 2011;McLarnon et al, 2020).…”
Section: A Comprehensive Program and Service Approach To Serving Unem...mentioning
confidence: 99%